Bayani, banyaga: A fictional novella about the lives of Mariano Ponce and Okiyo Udagawa - Jayme, Ma. Isabella C. (Animo Repository, 2013)
This creative writing thesis is a historical novella about my great great grandparents: a Philippine national hero, Mariano Ponce, and his Japanese wife, Okiya Udagawa, who was born of samurai lineage. Their story consists of their forbidden elopement and other significant events in their lives from the late Spanish period up until the Japanese occupation of the Philippines. It will be passed on my personal perspective of their story through Okiyo eyes by writing in third person point of view. This method not only provides an interesting depiction on the enemy (the Japanese) at the time. The novella will focus on the theme of her struggles with loyalties, i.e. between Okiyo samurai heritage and embracing the Filipino culture and religion as her own, and even choosing between Japanese troops and helping occupation of the Philippines such as Mario OHara film, Tatlong Taong Walang Diyos (1976) and Wilfrido Nolledo novel, But for the lovers (1970) by shedding light on the lives of actual historical figures as a more an opportunity to have a different perspective on the life of the barely recognized Mariano Ponce and his wife, at the same time helping me personally understand and explore my family history.